Strategic IQ creating smarter corporations - Wells, John R. (Jossey-Bass, 2012)
"Why do once-successful companies fail?The book identifies 3 types of inertia that can be fatal to the most successful company: strategic/structural/ personal. Senior executives often go to great lengths to resist change. When things start to go awry, they try harder (through efficiency gains, etc) and therefore may simply be getting better at doing the wrong thing. Instead they need to analyse their market effectively and diagnose what is needed to respond to the real threats outside. The illustrations throughout the book give the reader real-life tales of competition on the edge and show what took place behind the public narrative of many prominent companies. This book will prompt executives to ask: What is your Strategic IQ? Do you have the strategic intelligence to keep ahead of your competitors? Readers will find the book enlightening and its lessons easy to apply: It provides a framework for understanding strategic intelligence A roadmap for advancing up the intelligence ladder Assessment tools to measure progress John Wells shows how traditional success metrics such as revenue growth, profit, market share, reputation and stock price often fail to predict impending disaster - and what to do about it"--
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Strategic planning; Organizational effectiveness -- Management; Organizational change; Success in business; Organizational Innovation; Planification stratégique; Efficacité organisationnelle; Gestion; Changement organisationnel; Succès dans les affaires; BUSINESS & ECONOMICS; Decision-Making & Problem Solving; Organizational effectiveness; Management